Neurological examination in obsessive-compulsive disorder - Caramelli, Paulo; Lima, Mauro Aranha de; Stip, Emmanuel; Bacheschi, Luiz Alberto (São Paulo Medical Journal, 1996)
Recent studies suggest the occurrence of a neurological dysfunction in Obsessive-Compulsive Disorder (OCD). The purpose of the present study was to verify the clinical value of a neurological evaluation in patients with the disease. We submitted 15 patients with OCD (five of whom were under clomipramine) and 15 controls in a detailed neurological examination, including assessment of the neurological soft-signs. Eleven patients (73.3 percent) and four controls (26.7 percent) presented abnormalities on examination. The main findings among the patients were: palmomental reflex (six cases); mirror movements (five cases); agraphestesia and dysdiadochokinesia (three cases). Three out of the four patients who had a normal examination were on clomipramine. Palmomental reflex was the main finding among the controls. These results, although preliminary, stress the interest and usefulness of performing a detailed neurological examination in OCD.